Gambaran Tingkat Pengetahuan Pelihara Diri Kesehatan Gigi Dan Mulut Dengan Status Ohi-S Pada Remaja Karang Taruna - Winda Putri Yunita; Susilarti Susilarti; Dwi Eni Purwati (Poltekkes Kemenkes Yogyakarta, 2017)
The teenager is an era which affects someone life because in this era there are developing habit and behaviors which is related to oral and dental health. The oral and dental hygiene is extremely important to take care of an oral cavity from its plaque, karkar and many kinds of oral and dental diseases. OHI-S is an index which is used to measure someone’s oral and dental hygiene. OHI-S index is good if it is at 0-1,2 score. This research is to know about the oral and dental hygiene knowledge levels related to OHI-S index in the teenager on the youth organization. We could know about the oral and dental hygiene knowledge levels by the age factor, the last educational factor, parent’s job factor, and OHI-S index. This research is descriptive and uses Cross-Sectional survey approach. The method of collecting data conducted by questionnaires and check the oral and dental hygiene of the respondents. The result of the research indicates that there is a relation between the oral and dental hygiene in the teenager on the youth organization and the OHI-S index (72 %). The conclusion is the higher someone’s knowledge the better status of their oral and dental hygiene.